MANAGEMENT OF RETURN TO PHYSICAL ACTIVITY AFTER CONCUSSION: A SYSTEMATIC REVIEW - Agnieszka Burzej; Zofia Nowakowska; Wiktoria Dybizbańska; Mateusz Kacalak; Karolina Dziki; Aleksandra Marek; Julia Szklarska-Komenda; Katarzyna Garncarz; Maciej Komenda; Krzysztof Jamroch (International Journal of Innovative Technologies in Social Science, 2025)
Sport-related concussion management has undergone significant evolution, shifting from prolonged rest to active rehabilitation approaches. This systematic review examines current evidence regarding optimal return to physical activity protocols following sport-related concussion. A comprehensive literature search was conducted using PubMed, CINAHL, SPORTDiscus, and Web of Science databases, focusing on studies published between 2018-2023. Inclusion criteria comprised randomized controlled trials, systematic reviews, and prospective cohort studies examining physical activity interventions during concussion recovery. Contemporary evidence strongly supports brief initial rest (24-48 hours) followed by progressive, sub-threshold aerobic exercise. Multiple randomized controlled trials demonstrate that early controlled exercise accelerates recovery without adverse effects, reducing median recovery time from 17 to 13 days. The Buffalo Concussion Treadmill Test enables individualized exercise prescription at 80-90% of symptom-threshold heart rate. Multimodal approaches targeting specific symptom clusters (vestibular, cervicogenic, autonomic) show superior outcomes compared to generic protocols. Implementation remains inconsistent, with only 45% of practitioners regularly prescribing structured exercise despite strong evidence. Active rehabilitation through controlled, progressive exercise represents the current evidence-based standard for concussion management. Early sub-threshold aerobic exercise, initiated within one week of injury, optimizes recovery while minimizing persistent symptoms. Future research should focus on precision medicine approaches and optimal protocols for special populations.